Aorto-iliac-femoral thromboendarterectomy: An alternative to plastic prostheses - Arias, José; Galarraga, José A.; Lorenzelli, Juan; Segal, Marcos; Bogliaccini, Gustavo; Tchekmedjian, Vartan; Gastambide, Carmelo (Cirugía del Uruguay, 1979)
Uni - or bi - lateral extraperitoneal approach in aorto - iliac - femoral endartere. ctomy for treatment of obstructive arteriopathy in this sector, is considered a procedure for which there is precise indication, reduced technical complexity, low morbility and excellent result. The paper describes criteria for selection and indication, surgical technique employed and special instrumentation required. Case material consists of 48 operations in 40 patients and follow - up covers periods ranging from 2 to 94 months.